Perception of the dog and cat sterilization law (Law No. 31311) among residents of human settlements in the Ventanilla district, Callao, Peru, 2024 - Hinostroza, Camille (2025)
The objective of this study was to describe the perception of residents from four human settlements in the Ventanilla district, Callao (Peru), regarding the benefits and applicability of the law that prioritizes the sterilization of dogs and cats as part of the National Public Health Policy (Law No. 31311). A descriptive observational study was conducted using surveys administered to adult participants of both sexes, whether or not they owned a companion animal. A total of 400 valid surveys were obtained, of which 52.3% (n = 209) reported being aware of the law. Among these, 14.8% (n = 31) indicated that it had been implemented in the district, 56.5% (n = 118) stated that the municipality had funding for its execution, and 89.0% (n = 186) believed that this entity should finance sterilization campaigns in compliance with the law. Among all participants, 76.3% (n = 305) expressed willingness to sterilize their dogs or cats provided the cost was within their budget, whereas 23.7% (n = 95) would not. It is concluded that the limited information available to residents of human settlements in the Ventanilla district regarding Law No. 31311 constitutes a barrier to its effective implementation in the short term.